Human rights in brief - Clack, George; United States Department of State Bureau of International Information Programs; BC Open Textbook Project; BCcampus (Department of State Bureau of International Information Programs, 2008)
"In all civilized nations, attempts are made to define and buttress human rights. The core of the concept is the same everywhere: Human rights are the rights that one has simply because one is human. They are universal and equal. The following pubilcation gives an overview of Human Rights across the globe."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"15 March 2008"--Table of Contents on website version.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Human rights -- Textbooks; Electronic books